Continuous input-current buck-boost DC-DC converter for PEM fuel cell applications. (21st December 2017) - Valdez-Resendiz, Jesus E.; Sanchez, Victor M.; Rosas-Caro, Julio C.; Mayo-Maldonado, Jonathan C.; Sierra, J.M.; Barbosa, Romeli
Abstract: This paper proposes a buck-boost converter topology with continuous input-current capability for proton exchange fuel cells (PEMFC) systems. The continuous input-current feature of the converter contributes to maintain the PEMFC life-time, which is in sharp contrast with traditional buck-boost converters whose input currents damage the PEMFC and reduce the efficiency. Moreover, this converter offers the main advantages found in traditional topologies, such as the Cuk or the SEPIC converters, using a reduced number of electronic components. In particular, the topology features buck-boost conversion range capability, low input-current ripple, and a simple low-cost structure. A detailed analysis that encompasses steady state analysis, dynamic modelling, stability analysis, control and experimental results are provided. Highlights: A buck-boost converter with continuous input-current is proposed. The converter is proposed to be used for power conditioning of a PEMFC. The continuous input-current is achieved without increasing the number of parts. A design methodology and steady state analysis is provided for the converter. Experimental results with a Fuel Cell are provided to validate the proposition.